How to support your team when uncertainty is high - Fosslien, Liz (MIT Sloan Management Review, 2023)
Even in a turbulent environment where employees are facing job insecurity, leadership changes, or reorgs, managers can take steps to give their team members a sense of stability and help mitigate their anxiety. The author suggests seven ways managers can support their teams during times of instability to help restore employees’ sense of control and maintain their motivation.